2020
DOI: 10.21203/rs.3.rs-21603/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does internal limiting membrane peeling during epiretinal membrane surgery induce microscotomas on microperimetry? Study protocol for PEELING, a randomized controlled clinical trial

Abstract: Background The epiretinal membrane (ERM) is a degenerative condition associated with age, which can cause loss of vision and/or metamorphopsia. The treatment of symptomatic ERM involves surgical removal including a vitrectomy followed by peeling of the ERM using a microforceps. As the internal limiting membrane (ILM) is adherent to the ERM, it is sometimes removed with it (spontaneous peeling). If ILM remains in place, it can be removed to reduce ERM recurrence. However, it is important to clarify the safety o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Previous studies indicated that the Müller cell activation might contribute to its formation. 17 The ILM peeling during the ERM removal will increase the risk of histological disorganization of the retina but with no impairment of VA. 3,25 This procedure can result in significant damage to the Müller cells, promoting the reparation of injury of the Müller cells. Therefore, the presence of EIFL postoperatively may represent a repair response to the surgical damage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the Müller cell activation might contribute to its formation. 17 The ILM peeling during the ERM removal will increase the risk of histological disorganization of the retina but with no impairment of VA. 3,25 This procedure can result in significant damage to the Müller cells, promoting the reparation of injury of the Müller cells. Therefore, the presence of EIFL postoperatively may represent a repair response to the surgical damage.…”
Section: Discussionmentioning
confidence: 99%